Оцінювання та державне регулювання систем краудфандингу в національній економіці - Уголькова, Олена Зіновіївна (Національний університет "Львівська політехніка", 2019)
Дисертацію присвячено вирішенню наукового завдання розроблення теоретичних положень та надання методико-прикладних рекомендацій з удосконалення підходів до оцінювання та державного регулювання систем краудфандингу. У роботі розвинуто понятійний та термінологічний апарат щодо систем краудфандингу та удосконалено типологію краудфандингових проектів. Проведено детальний аналіз досвіду застосування краудфандингу та виявлено чинники, що вплинули на встановлення та розвиток краудфандингової діяльності у розвинених країнах світу. Розвинуто типологію чинників розвитку краудфандингу та досліджено їх вплив на вітчизняні реалії. Удосконалено положення з державного регулювання краудфандингу. Розроблено модель процесу реалізації краудфандингового проекту, систематизовано та вдосконалено ряд показників з метою здійснення оцінювання та моніторингу стану краудфандингової діяльності. Диссертация посвящена решению научной задачи разработки теоретических положений и методико-прикладных рекомендаций по совершенствованию подходов к оценке и государственному регулированию систем краудфандинга. В работе развит терминологический аппарат по системам краудфандинга и усовершенствована типология краудфандинга. Проведен детальный анализ опыта применения краудфандинга и выявлены факторы, повлиявшие на установление и развитие краудфандинговои деятельности в развитых странах мира. Развито типологию факторов развития краудфандинг и исследовано их влияние на отечественные реалии. Разработана модель процесса реализации краудфандингового проекта, которая разделяет проект на этапы с выделением ответственных за каждый этап лиц и их функций. Усовершенствована положения по государственному регулированию краудфандинга и систематизировано ряд показателей с целью осуществления оценки и мониторинга состояния краудфандинговои деятельности в государстве. The dissertation is devoted to solving the scientific problem of developing theoretical basis and providing methodological and applied recommendations for improving approaches to the evaluation and state regulation of the crowdfunding systems. The relevance of scientific research is due to the limited financial resources and their significant cost for newly created, innovative enterprises or for public organizations and diverse cultural and artistic associations. The object of the research of the dissertation is the process of assessment and state regulation of the crowdfunding system, and the subject of the study is the theoretical and applied principles of state regulation of the crowdfunding activity in the conditions of development of the domestic market. The conceptual and terminological apparatus in relation to crowdfunding activity is developed, namely the author's definition of the notions "crowdfunding", "crowdfunding system", "crowdfunding project", "crowdfunding activity" and others is given. In author’s opinion, crowdfunding is an innovative tool that allows accumulation of financial resources from a significant number of participants (donors) for the implementation by authors (recipients) of innovative, social and business projects with the use of specialized Internet resources (crowdfunding platforms) requiring special competencies from recipients, which may affect the donor's positive decision. The system of crowdfunding, in author’s understanding, is a combination of the activities of crowdfunding actors, that are, the project authors, the donors (sponsors) of the project and the intermediaries thanks to Internet resources in order to accumulate funds for the implementation of innovative, business and social projects In addition, the typology of crowdfunding projects is improved, new classification features and new types of crowdfunding projects are proposed and the analysis of the main selected types is realized. Namely, it is proposed to take into account such classification features as novelty and information channel of the project. The author distinguishes the following types of projects by the novelty: radical, modernization and non-innovative projects. The radical crowdfunding project is type of project that allows the creation of new product or service, modernization project has a purpose to improve certain existing products and services, and non-innovative project is a project that requires financial help for the implementation or creation of existing ideas, goods, services, and events. According to the information channels of project, the crowdfunding projects can be divided into projects with direct and indirect channel of information. The development of such a typology will create the basis for an adequate legal framework that will not manage crowdfunding activity in general, but each individual type of crowdfunding project, since each one is significantly different from the other by the crowdfunding platforms, by the way of rewarding, and by participants. The model of the implementation of the crowdfunding project is developed in the dissetation. This model divides the project into stages with the identification of those responsible for each stage of the individuals and the allocation of their functions. The mains functions at all stages of projects for recipients are the following: development of the concept of crowdfunding project; choice of appropriate crowdfunding platform and registration of project; choice of monetary purpose, duration of the campaign, remuneration for donors; preparation of the necessary information tools (video, content, etc.) and promotion in the media, social networks; communication with existing and potential crowdfunding project’s donors; update information and reporting; receiving funds and implementation of idea of crowdfunding project; informing donors about the project’s results and their remuneration. Detailed analysis of the experience of applying crowdfunding in developed countries is carried out. As a result, the typology of the factors of development of crowdfunding is developed and the influence of these factors on the national realities is analyzed. In the dissertation, the concept of "state regulation of crowdfunding activity" is improved. The author suggests to include the following instruments for state regulation of crowdfunding systems: improvement of the legal and regulatory framework governing such activity; stimulating tax policy and tax incentives for the implementation of crowdfunding projects; provision of a mechanism for the development of business incubators, accelerators and other elements of innovation infrastructure; development and implementation of a mechanism for disseminating information about crowdfunding as financial instrument (creation of Ukrainian association of crowdfunding, different state offices, etc.); creation of preconditions and regulation of cooperation with international and Ukrainian crowdfunding internet platforms. In order to realize the evaluation and continuous monitoring of crowdfunding activity, it is suggested to use the following indicators: the total amount of financial resources accumulated with the help of crowdfunding, the total number of crowdfunding platforms existing in a particular state, the average amount of financial resources accumulated with the help of one crowdfunding project, the weight of the contribution of the crowdfunding activity to GDP, the share of number of participants in the crowdfunding activity in the total number of economically active population, the weight of the contribution of the crowdfunding activity to the economic activity of the state, the indicator of financial feasibility of applying crowdfunding. These indicators can be used to assess crowdfunding activity. Initial calculations on these indicators showed the prospect of such an assessment approach. The positive dynamics of these indicators will characterize the high quality of public administration and will allow for comparative analysis both at the state and at the regional level. The practical significance of the results obtained in the dissertation is the possibility of using financial managers of existing enterprises and young entrepreneurs methodical recommendations for: substantiation of expediency of attraction of financial resources with the help of crowdfunding activity; development of the crowdfunding project and establishment of responsible persons at each stage of the project; analysis of the project on its viability; estimation of economic efficiency of the crowdfunding project. In addition, the research results constitute a solid foundation for further research in this area.
Оценивания и государственное регулирование систем краудфандинга в национальной экономике
Evaluation and state regulation of crowdfunding systems in the national economy
Keywords: краудфандинг; фінансування; інновації; система; регулювання краудфандингової діяльності; краудфандинг; финансирование; инновации; система; регулирования краудфандинговои деятельности; crowdfunding; financing; innovation; system; regulation of crowdfunding activity; 330.322.14.025.12(477)(043.5)